Innate Immunity Evasion Strategies of Highly Pathogenic Coronaviruses: SARS-CoV, MERS-CoV, and SARS-CoV-2 - Li, Jin-Yan; Zhou, Zhi-Jian; Wang, Qiong; He, Qing-Nan; Zhao, Ming-Yi; Qiu, Ye; Ge, Xing-Yi (Frontiers in Microbiology, 2021)
In the past two decades, coronavirus (CoV) has emerged frequently in the population. Three CoVs (SARS-CoV, MERS-CoV, SARS-CoV-2) have been identified as highly pathogenic human coronaviruses (HP-hCoVs). Particularly, the ongoing COVID-19 pandemic caused by SARS-CoV-2 warns that HP-hCoVs present a high risk to human health. Like other viruses, HP-hCoVs interact with their host cells in sophisticated manners for infection and pathogenesis. Here, we reviewed the current knowledge about the interference of HP-hCoVs in multiple cellular processes and their impact on viral infection. HP-hCoVs employed various strategies to suppress and evasion from immune response, including shielding viral RNA from recognition by pattern recognition receptors (PRRs), impairing IFN-I production, blocking the downstream pathways of IFN-I, and other evasion strategies. This summary provides a comprehensive view of the interplay between HP-hCoVs and the host cells, which is helpful to understanding the mechanism of viral pathogenesis and developing antiviral therapies.